2013
DOI: 10.2298/gsf1308067k
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low initial medium pH on in vitro white poplar growth

Abstract: The effect of low initial medium pH on shoot and root development of five white poplar (Populus alba L.) genotypes was tested. The shoot height, fresh mass of shoots per jar, dry mass of shoots per jar, number of roots, as well as the length of the longest root were measured and final pH of the media determined, after 35 days of culture in vitro. Three initial pH values of the medium were tested: 3.0, 4.0 and 5.5 as control. Agar solidification at pH 3.0 was not achieved after sterilization in autoclave,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
1
6
0
1
Order By: Relevance
“…However, medium with pH 5.5 significantly enhanced forming roots in 21.89 days compared to medium pH at 5 where roots were formed in 25.11 days. Similar results were reported by Martins et al (2011) on Plantago lmogravensis, Kovacevic et al (2013) on poplar. Also, Ahmed et al (2014) reported that Musa spp.…”
Section: Effect Of Medium Ph Naa Concentrations and Their Interactionsupporting
confidence: 89%
“…However, medium with pH 5.5 significantly enhanced forming roots in 21.89 days compared to medium pH at 5 where roots were formed in 25.11 days. Similar results were reported by Martins et al (2011) on Plantago lmogravensis, Kovacevic et al (2013) on poplar. Also, Ahmed et al (2014) reported that Musa spp.…”
Section: Effect Of Medium Ph Naa Concentrations and Their Interactionsupporting
confidence: 89%
“…In our work we conducted the test at pH 3, using citric acid to lower and stabilize the pH. It is well known that the pH of the media could be altered by many factors during both sterilization and cultivation in vitro [21]. Citric acid Lables of examined media: C0 -10 -7 Cu 2+ , pH 5.5, C1 -10 -7 Cu 2+ , pH 3, C2 -10 -4 Cu 2+ , pH 3, C3 -10 -3 Cu 2+ , pH 3 before autoclaving 2…”
Section: Discussionmentioning
confidence: 99%
“…The number of roots and the percentage of rooted shoots were significantly higher on C1; however, the shoot height and shoot dry mass on this medium were similar to those on C0. Kovačević et al [21] observed significant growth and improved development of white poplar with regard to both shoot and root in plants grown in vitro on medium with an initially low (before sterilization) pH of 3.0. The authors did not use citric acid nor any additional buffer system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Као контролни третман коришћена је ACM подлога за ожиљавање без NaCl. Подлога је стерилисана у микроталасној пећници (Kovačević et al, 2013a). Културе су узгајане у стерилним стакленим бочицама запремине 120 mL са по 25 mL подлоге на температури од 26 ± 2°C и биле су изложене белој светлости LED лампи од 3500 lx у 16h/8h режиму дан/ноћ.…”
Section: материјал и методе радаunclassified